Perioperative Analgesic Efficacy of Yamamoto New Scalp Acupuncture for Canine Mastectomy Combined with Ovariohysterectomy: a Randomized, Controlled Clinical Trial - Carolina de Carvalho Bacarin; Gabriel Montoro Nicácio; Letícia Maria de Lima Cerazo; Luíza Guimarães Peruchi; Renata Navarro Cassu (Medical Association of Pharmacopuncture Institute, 2022)
Background : Yamamoto New Scalp Acupuncture (YNSA) is a therapy based on the stimulation of points on the scalp and applied to treat different states of pain. Objectives: To investigate the analgesic efficacy of YNSA for dogs undergoing radical unilateral mastectomy with ovariohysterectomy. Methods : Twenty-four dogs were randomly distributed into two treatments (n = 12, per group): bilateral stimulation of basic B, D, and E points (YNSA group) and no application of acupuncture (control group). All dogs were sedated with morphine; anesthesia was induced with propofol and maintained with isoflurane. Fentanyl was intraoperatively administered to control cardiovascular responses to surgical stimulation. Postoperative pain was assessed using an interactive visual analog scale (IVAS) and the short-form of the Glasgow Composite Pain Scale (CMPS-SF). Morphine was administered as rescue analgesia. Data were analyzed using t-tests, Fisher's exact test, Mann-Whitney U test, and Friedman test (p > 0.05). Results : Intraoperatively, the number of dogs requiring supplemental analgesic and the number of doses of fentanyl were lower in the YNSA group than in the control group (p = 0.027-0.034). The IVAS pain scores recorded from 0.5 h to 1 h post-extubation in the YNSA group were lower than those in the control group (p = 0.021-0.023). Postoperative rescue analgesia and CMPS-SF pain scores did not differ between the groups. Conclusion : YNSA decreases intraoperative fentanyl requirements and provides minimal postoperative analgesic benefits to dogs undergoing unilateral mastectomy with ovariohysterectomy.